PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI MIPA SMAPERTIWI 1 PADANG - Baene, Gustimawati K (Jurnal Edukasi dan Penelitian Matematika, 2023)
Students should learn effective arithmetic problem-solving techniques as one of their learning objectives in mathematics. Nonetheless, pupils still have a limited capacity for solving mathematical puzzles. Learning methods that use problem-based learning (PBL) are one way to help students get better at solving problems. This study aims to compare the problem-solving skills of students who learn using a problem-based learning model with those of students who learn using direct instruction. It also aims to describe how students' mathematical problem-solving skills develop when they apply a problem-based learning learning model in class XI MIPA SMA Pertiwi 1 Padang. This sort of study uses a quasi-experimental design with a posttest-only grouping that is not equivalent.Students in class XI MIPA SMA Pertiwi 1 Padang in yhe academic year 2022–2023 make up this population, with class XI MIPA 3 serving as the experimental class and XI MIPA 2 serving as the control class. Research data was gathered by testing and quizzing students on their problem-solving skills. Based on the average score and the proportion of students who scored well on each indication, the value data quiz was analyzed. T-test data analysis is used.  Keywords:PBLLearningModel,ProblemSolvingMathematical,Pseudo-Experiments